STRUCTURING AXES THAT GUIDE PEDAGOGICAL PRACTICES: INTERACTIONS AND PLAY IN EARLY CHILDHOOD EDUCATION - Aparecida Gonçalves Ribeiro, Patrícia; Frizzera, Cristiane; Rodrigues de Souza Bassiqueti, Elaine; Aparecida Rocha da Silva, Eliane; Gouvêa de Souza, Elisângela; Alessandra dos Santos, Fabiana; Luzes Galvão, Gabrielle; Aparecida da Silva Moura, Maria; Berbel dos Santos, Roseli; Alves de Souza, Silvane; Rodrigues de Oliveira, Maurenice; Costa Wathier dos Santos, Juliana; et al. (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to reflect on the importance of games and interactions as guiding principles of educational practices in Early Childhood Education, being indispensable for the construction of meaningful learning in the school environment. Therefore, the research is based on the main advances established in legislation and addresses interactions and games in the school context as fundamental axes of pedagogical practice. In this sense, it is based on bibliographical research with a qualitative approach. To this end, bibliographical research was carried out on sites such as Google Scholar, SciELO, among others relevant to the subject, in order to have a basis, the National Curricular Guidelines for Early Childhood Education, National Common Curricular Base, articles, monographs and dissertations with publications on the theme. In this light, we can say that the theme is relevant, indispensable and extremely relevant, since games and interactions contribute to the development of children with such intensity and in such a remarkable way that they represent a solid foundation for their entire lives and it is the It is from early childhood education that it is possible to form good, thinking citizens who are mainly committed to society.